Clinicopathological characteristics, treatments and oncological outcomes in metaplastic breast cancer: a Brazilian multicenter analysis - Mendes, Talita Aparecida Riegas; de Oliveira-Junior, Idam; Brenelli, Fabrício Palermo; Cardoso-FIlho, Cassio; Zeferino, Luiz Carlos (Frontiers in Oncology, 2025)
IntroductionMetaplastic breast carcinoma (MBC) is a highly heterogenous group of tumors. MBC differs from other invasive carcinomas in clinical presentation, prognosis and response to treatment. The tumor is more aggressive and the most effective form of treatment is still uncertain for this patient population, given the particularities of the disease.Subjects and methodsThis is a retrospective, descriptive study analyzing data from women admitted for MBC treatment to participating centers (Hospital de Amor, Barretos, and Center for Integral Attention to Women’s Health, CAISM/UNICAMP) between 2010 and 2020.ResultsA total of 102 women with pathologically confirmed MBC and presenting non-metastatic disease were included. The average age at diagnosis was 53 years, 73.3% were triple-negative (TN) subtype and mean tumor size at diagnosis was 7.4 cm. We found that 59% of patients were clinical stage III at diagnosis and 82.3% of the cases underwent mastectomy. Despite the use of neoadjuvant treatment in 52.9% of patients, the pathological complete response (pCR) rate was only 7.4%. Around 46% of patients underwent adjuvant chemotherapy and 79.4% received adjuvant radiotherapy. We observed a 5-year overall survival (OS) of 59,7% and a 5-year disease-free survival (DFS) of 54.4%. Adjuvant chemotherapy, smaller tumor size and absence of lymph node disease were associated to better DFS and OS.ConclusionMBC presented as a large nodular lesion at diagnosis, the most frequent metaplastic subtypes presented squamous and mesenchymal differentiation, almost 80% were triple-negative tumors, however, responses to neoadjuvant chemotherapy can be considered poor. A higher number of metastatic lymph nodes and larger tumor size were associated with worse DFS and OS, meanwhile the women who undergone to adjuvant chemotherapy showed better DFS and OS. Furthermore, most recurrences occurred in the first 24 months of follow-up, stabilizing at approximately 50% after 36 months, and most deaths occurred in the first 36 months, stabilizing thereafter, which is a clinical pattern of very aggressive tumors.